Exposure to melamine and its derivatives and aromatic amines among pregnant women in the United States: The ECHO Program. (November 2022) - Choi, Giehae; Kuiper, Jordan R.; Bennett, Deborah H.; Barrett, Emily S.; Bastain, Theresa M.; Breton, Carrie V.; Chinthakindi, Sridhar; Dunlop, Anne L.; Farzan, Shohreh F.; Herbstman, Julie B.; Karagas, Margaret R.; Marsit, Carmen J.; et al.
Abstract: Background: Melamine, melamine derivatives, and aromatic amines are nitrogen-containing compounds with known toxicity and widespread commercial uses. Nevertheless, biomonitoring of these chemicals is lacking, particularly during pregnancy, a period of increased susceptibility to adverse health effects. Objectives: We aimed to measure melamine, melamine derivatives, and aromatic amine exposure in pregnant women across the United States (U.S.) and evaluate associations with participant and urine sample collection characteristics. Methods: We measured 43 analytes, representing 45 chemicals (i.e., melamine, three melamine derivatives, and 41 aromatic amines), in urine from pregnant women in nine diverse ECHO cohorts during 2008–2020 (N = 171). To assess relations with participant and urine sample collection characteristics, we used generalized estimating equations to estimate prevalence ratios (PRs) for analytes dichotomized at the detection limit, % differences (%Δ) for continuous analytes, and 95% confidence intervals. Multivariable models included age, race/ethnicity, marital status, urinary cotinine, and year of sample collection. Results: Twelve chemicals were detected in >60% of samples, with near ubiquitous detection of cyanuric acid, melamine, aniline, 4, 4′-methylenedianiline, and a composite of o-toluidine and m-toluidine (99–100%). In multivariable adjusted models, most chemicals were associated with higher exposures among Hispanic and non-Hispanic Black participants. For example, concentrations of 3, 4-dichloroaniline were higher among Hispanic (%Δ: +149, 95% CI: +17, +431) and non-Hispanic Black (%Δ: +136, 95% CI: +35, +311) women compared with non-Hispanic White women. We observed similar results for ammelide, o-/m-toluidine, 4, 4′-methylenedianiline, and 4-chloroaniline. Most chemicals were positively associated with urinary cotinine, with strongest associations observed for o-/m-toluidine (%Δ: +23; 95% CI: +16, +31) and 3, 4-dichloroaniline (%Δ: +25; 95% CI: +17, +33). Some chemicals exhibited annual trends (e.g., %Δ in melamine per year: −11; 95% CI: −19, −1) or time of day, seasonal, and geographic variability. Discussion: Exposure to melamine, cyanuric acid, and some aromatic amines was ubiquitous in this first investigation of these analytes in pregnant women. Future research should expand biomonitoring, identify sources of exposure disparities by race/ethnicity, and evaluate potential adverse health effects. Graphical abstract: Image 1 Highlights: Measured four melamine derivatives and 41 aromatic amines in ECHO pregnant women. Melamine, cyanuric acid, and ten aromatic amines detected in >60% of women. Concentrations higher in non-Hispanic Black or Hispanic women for several compounds. Most chemicals positively associated with the tobacco biomarker cotinine. Annual, within-day, seasonal, and geographic variability observed.